Prácticas de la enseñanza de las matemáticas en educación general básica :análisis de caso en segundo año en la Escuela Belén 15 de julio de la Comunidad Guayama - Gavilanes Llanqui, Juan Rafael (2016)
The present research work on "practice in the teaching of mathematics in basic General education. Analysis of case, in second year in the Bethlehem school July 15, Guayama community", where residents and students belong to the indigenous culture. According to research it was concluded in the Ecuador there are no exclusive documents on "pedagogical practices" in the area of mathematics. Therefore, this work, sought attention and point out the teaching practice in the area of math, in the second year of basic education, in activities that made a teacher in its class such as: curriculum planning, compliance with the process of teaching - learning, distribution and organization of the classroom class, teachers – children’s interaction is the most important part in education assessment and types of academic tasks. Bibliographical research concerning teaching practice and its models, second-year mathematics and teaching procedure was performed; after the respective systematization and analysis of information collected on direct observations of classes, it presents main results, which highlights that the teacher uses elements of each of the types and models of teaching practice, but excels teaching practice as technical activity that is related to the normative model, where the teacher is the protagonist of passing knowledge to the student and the student listen, learn, attend then imitates, train, exercise and apply. Thus, neglecting practice and understanding of meaning and practice as a space for cultural exchanges.